2016
DOI: 10.1093/inthealth/ihw040
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from the Obio Community Health Insurance Scheme in Rivers State, Nigeria? A benefit incidence analysis

Abstract: Although the poor were found to benefit, this BIA revealed a tendency towards pro-rich distributions. Removing co-payments for the poorest, reducing long wait and visit times and using community volunteers to help increase access to health services may improve benefits for the poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This study reveals a disproportionate concentration of inpatient care benefits among richer individuals and demonstrates that the rich received a greater amount of benefits than did the poor, in agreement with prior studies [ 21 , 32 ]. In addition, we observed that this inequality among NRCMS enrollees was greater than that among URBMI participants, also in agreement with prior reports [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study reveals a disproportionate concentration of inpatient care benefits among richer individuals and demonstrates that the rich received a greater amount of benefits than did the poor, in agreement with prior studies [ 21 , 32 ]. In addition, we observed that this inequality among NRCMS enrollees was greater than that among URBMI participants, also in agreement with prior reports [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Divorced, single or separated individuals received significantly less reimbursements, indicating that marriage and family life are economically and spiritually positive factors in the effective utilization of available healthcare options. People with a higher education received more net benefits, in agreement with existing literature [ 32 ]. Higher education level is a marker of the ability to turn information into practical behaviors, resulting in a best use of healthcare.…”
Section: Discussionsupporting
confidence: 89%
“…40 Some of these studies used concentration index and benefit analysis to provide stronger evidence of equity of utilisation. 43,[49][50][51][52][53] Two studies reported different findings; an insignificant difference in CBI scheme in Rwanda 45 and a study conducted in Tunisian found pro-poor distribution of benefits in both national and community-based health insurance schemes 51 .…”
Section: Place Of Residencementioning
confidence: 99%